Den of thieves [videorecording (DVD)] - Gudegast, Christian; Butler, Gerard, 1969-; Schreiber, Pablo; Jackson, O'Shea, Jr., 1991- (Universal Pictures Home Entertainment, 2018)
A gritty crime saga which follows the lives of an elite unit of the LA County Sheriff's Dept. and the state's most successful bank robbery crew as the outlaws plan a seemingly impossible heist on the Federal Reserve Bank.